2022
DOI: 10.3390/medicina58081097
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Associations across Fibromyalgia-Related Fatigue, Depression, Anxiety, Self-Esteem Satisfaction with Life and Physical Activity in Portuguese and Brazilian Patients: A Structural Equation Modeling Analysis

Abstract: Background and Objectives: Fibromyalgia are heterogeneous and differ from patient to patient; however, the most reported are general myalgia and at specific points associated with fatigue and certain psychological adversities. Physical activity can mitigate the effects of the symptoms. However, the associations between fibromyalgia-related fatigue, self-esteem, anxiety, depression, satisfaction with life and physical activity are unclear. Therefore, the aim of the present study was to understand the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Fibromyalgia (FM) exists in 2-8% of the population, and is characterized by extensive pain, which is often accompanied by fatigue, memory problems, and sleep disorders (1,2). Although FM has been excluded from the diagnosis of neuropathic pain since the revision of the International Association for the Study of Pain (IASP) definition of neuropathic pain in 2011, recent studies have found that about 50% of FM patients have neuropathic changes of small and/or large fibers (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Fibromyalgia (FM) exists in 2-8% of the population, and is characterized by extensive pain, which is often accompanied by fatigue, memory problems, and sleep disorders (1,2). Although FM has been excluded from the diagnosis of neuropathic pain since the revision of the International Association for the Study of Pain (IASP) definition of neuropathic pain in 2011, recent studies have found that about 50% of FM patients have neuropathic changes of small and/or large fibers (3,4).…”
Section: Introductionmentioning
confidence: 99%